Unpowered Scooter Injury in Children at a Korea Level I Trauma Center - Keum, Min Ae; Cho, Min Jeng (Frontiers in Pediatrics, 2021)
Purpose: Unpowered scooters for recreation and transportation are popular among children. However, to date, there have been no studies on scooter-related injuries in Korea. This study aimed to assess the frequency and injury pattern with unpowered scooters and to propose prevention strategies. Methods: Medical records of children aged <16 years with unpowered scooter-related injuries who visited the emergency department from 2007 to 2018 were retrospectively reviewed. Results: A total of 109 children were included. The majority (78.9%) of injuries occurred during the last 3 years of the study. The mean age was 5.2 years, and 88% of children were <8 years of age. Most injuries (80.7%) occurred from a fall off a scooter. A total of 65.1% (n=71) of injuries were to the head and face, followed by upper limb, lower limb, and torso injuries. Eight patients had an intracranial injury and skull fracture. Twenty children had limb fractures, and the most common site of fracture was the elbow. None of the patients wore any protective gear. Conclusions: Unpowered scooter-related injuries are on the increase and are particularly a serious problem among younger children. The head and face, where serious injuries can occur, are the most vulnerable. Public and parental awareness and education regarding protective gear and safety guidelines are essential to prevent injuries.